Pengaruh Gender, Tekanan Ketaatan, Kompleksitas Tugas, Pengalaman Auditor, Pengetahuan Auditor, Dan Kompleksitas Dokumen Audit Terhadap Audit Judgement: - Tri Hastuti Komalasari; Efrizal Syofyan; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2019)
The purpose of this research is to know the: (1) the influence of Gender against the audit Judgement, (2) the influence of Pressure adherence to audit judgement, (3) the influence of task Complexity against audit judgement, (4) the influence of the experience of the auditors against Audit Judgement, (5) the influence of the knowledge of Auditors Audit against the Judgement, and (6) the influence of the complexity of the Audit the Audit Judgement against the Document. The population in this research is the whole BPK Auditors in West Sumatra. The sample in this research is as many as 64 people auditor. Data collection techniques used by spreading the questionnaire directly to the parties concerned. Analysis techniques are used is multiple regression. The research results showed that: (1) Gender has no effect against the audit judgement, (2) the pressure of the adherence to the audit judgement has no effect, (3) the complexity of the task has no effect against the audit judgement, (4) the auditor not experience effect on audit judgement, (5) knowledge of the audit to the auditor's judgement, and (6) the complexity of the audit document has no effect against the audit judgement.